BEYOND THE PUBLIC HEALTH NARRATIVE: ABSTINENCE-ONLY EDUCATION IN THE UNITED STATES - Angelica Raras Anindiati Ningtyas; Dewi H. Susilastuti (Sanata Dharma University, 2022)
This research studies the intention and endeavour of Christian-based organizations, namely the Family Research Council and Family Policy Alliance in disseminating the notion of sexuality in American society. This research utilizes a narrative analysis strategy and employs the following steps: 1) close reading the collected documents; 2) categorizing the recurring patterns of narratives using sociological perspective and cultural reproduction theory; 3) drawing a conclusion on the intention and efforts of Family Research Council and Family Policy Alliance in spreading the knowledge of sexuality. Using the narratives of aspirations and tensions which surrounds sexuality, this study shows that Family Research Council and Family Policy Alliance uphold Christian values as the organization's foundation and attempt to secure those principles in the ‘sex-saturated society.’ To accomplish the mission, Family Research Council and Family Policy Alliance promote abstinence-only education and oppose comprehensive sex education, arguing that comprehensive sex education holds liberal values that threaten the sanctity of the heterosexual relationship. This research demonstrates that Family Research Council and Family Policy Alliance, as Christian-based organizations, strive to preserve the conservative values that have been passed down from generation to generation.